2018
DOI: 10.1371/journal.pone.0204127
|View full text |Cite
|
Sign up to set email alerts
|

ACE gene haplotypes and social networks: Using a biocultural framework to investigate blood pressure variation in African Americans

Abstract: Deaths due to hypertension in the US are highest among African Americans, who have a higher prevalence of hypertension and more severe hypertensive symptoms. Research indicates that there are both genetic and sociocultural risk factors for hypertension. Racial disparities in hypertension also likely involve genetic and sociocultural factors, but the factors may interact and manifest differently across racial groups. Here we use a biocultural approach to integrate genetic and social network data to better under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…Researchers typically invoke social networks as a source of social support, but personal networks can also be a source of strain. In a previous study with the same population of African Americans, we found that systolic and diastolic blood pressure were significantly elevated in individuals with networks dominated by family members [28]. In the current study, we show that depression is associated with the percentage of the network comprised of people who cause participants stress or worry.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Researchers typically invoke social networks as a source of social support, but personal networks can also be a source of strain. In a previous study with the same population of African Americans, we found that systolic and diastolic blood pressure were significantly elevated in individuals with networks dominated by family members [28]. In the current study, we show that depression is associated with the percentage of the network comprised of people who cause participants stress or worry.…”
Section: Discussionsupporting
confidence: 66%
“…Social networks are being used more frequently to quantify aspects of an individual's social environment. Variation in network composition and structure have been linked to a range of outcomes including happiness, obesity, and blood pressure [26][27][28]. Researchers typically invoke social networks as a source of social support, but personal networks can also be a source of strain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Fuller et al tested whether social network structure influenced the well-established association of angiotensin 1 converting enzyme gene (ACE) with hypertension among African Americans. Inclusion of both genetic haplotype and family social structure measures yielded a better fitting predictive model for both systolic and diastolic blood pressure compared to either component alone [14]. In the clinical setting, others have demonstrated how incorporating genetic risk information into primary care discussions can lessen patient perceptions of personal blame that can inhibit their receptivity to providers' weight management recommendations [15].…”
Section: Introductionmentioning
confidence: 99%